St. Augustine America's Oldest City - Wade, Linda R (Rourke Enterprises, Inc. Vero Beach, Florida, 1991)
An introduction to the history and present-day attractions of the oldest city in the United States.
Includes index
Keywords: Saint Augustine (Fla.) -- History -- Juvenile literature; Saint Augustine (Fla.) -- Description -- Juvenile literature